Co-infestation caused by Goniodes pavonis (L., 1758) (Ischnocera: Goniodidae) and Goniocotes rectangulatus Nitzsch [In Giebel], 1866 on white Indian peafowl, Pavo cristatus L., 1758 (Galliformes: Phasianidaede) in Brazil - Bassini-Silva, Ricardo [UNESP]; Calchi, Ana Cláudia [UNESP]; Castro-Santiago, Ana Carolina; Siconelli, Márcio Junio Lima; André, Marcos Rogério [UNESP]; Barros-Battesti, Darci Moraes [UNESP]; Jacinavicius, Fernando de Castro (Elsevier, 2024)
The genus Goniodes Nitzsch and Goniocotes Burmeister (Ischnocera: Goniogodidae) are distributed worldwide, and exclusively parasitizing avian hosts of the Galliformes. In Brazil, there are only four species recorded: Goniodes dissimilis Denny, Goniodes gigas (Taschenberg), Goniodes pavonis (L.), and Goniocotes gallinae (DeGeer). In the present study, we are reporting the co-parasitism of G. pavonis and G. rectangulatus Nitzsch [In Giebel] on specimens of the white Pavo cristatus, popularly known as ‘white Indian peafowl’ for the first time. Furthermore, a new Brazilian locality for G. pavonis species has been reported, as well as the first time that G. rectangulatus is reported to Brazil. Additionally, we provide the first molecular information for G. pavonis.
Keywords: Chewing louse; Ectoparasites; Indian peafowl; Invasive birds; Molecular data